Idiopathic scoliosis in children and adolescents – a literature review - Grabala, Pawel (Journal of Education, Health and Sport, 2019)
Background: Scoliosis is defined as a lateral deviation from the normal vertical line of the vertebral column. Idiopathic scoliosis is a term for a disease entity that is a three-dimensional curve of the vertebral column. Idiopathic scoliosis is extremely rare in the neonatal and the early childhood period, and its prevalence among adolescents up to 15 years of age is estimated between 1% and 2%. The consequences of the development of the disease may include reduced mobility of the vertebral column, spinal pain, limitation of the vital capacity of the lungs and in the psychological aspect – problems with accepting one’s appearance, low self-esteem, leading to the development of depressive disorders. Material and methods: Analysis of available literature, articles in the Google Scholar database and PubMed using keywords: scoliosis, idiopathic scoliosis, pediatric deformities. Results: Knowledge of natural history, the prevalence of idiopathic scoliosis and the physiology and pathophysiology of the growth of the vertebral column are indispensable factors to determine if a treatment is necessary, and if so, which one. The occurrence of larger curves of above 30 degrees is estimated at between 0.15% and 0.3%. Weinstein created a table of calculations that show a decreasing prevalence with increasing curve size. The importance of these tests in the assessment of curve is that small scoliosis is common, but greater curves are much less common. Less than 10% of children with a curve value of 10 degrees or more require treatment. Conclusions: Thoracic idiopathic scoliosis greater than 50 degrees in adult age may gradually deteriorate and potentially reduce lung function. Lumbar curves, especially those greater than 50 degrees, can also develop in adult age and lead to osteoarthritis. Curves between 30 and 50 degrees may demonstrate a slight progression in adult age, but are generally stable. Therefore, even if cosmetic factors are not considered, it is justified to aggressively treat a child with a significant deformity of the vertebral column.